Niemann-Pick C2 Proteins: A New Function for an Old Family - Zhu, Jiao; Guo, Mengbuo; Ban, Liping; Song, Li-Mei; Liu, Yang; Pelosi, Paolo; Wang, Guirong (Frontiers in Physiology, 2018)
Niemann-Pick proteins type C2 (NPC2) are carriers of cholesterol in vertebrates, with a single member in each species. The high sequence conservation between mammals and across vertebrates is related to their common function. In contrast, NPC2 proteins in arthropods have undergone extensive duplication and differentiation, probably under environmental pressure, and are likely to have different functions. Recent studies have suggested that in arthropods these proteins might act as carriers for semiochemicals and other hydrophobic compounds. In this study we focused on the function of a specific NPC2 gene in the moth Helicoverpa armigera (HarmNPC2-1). This protein binds several flavonoids with micromolar dissociation constants. The best ligand was gossypol, present in cotton, one of the main host plants for H. armigera. Western blot revealed the presence of HarmNPC2-1in different parts of the body, including the antennae, proboscis, and abdomen. In the antennae, in situ hybridization experiments produced strong staining in auxiliary cells at the base of sensilla trichodea, basiconica, coeloconica, and chaetica. Immunocytochemistry confirmed the expression of the protein in sensilla chaetica. Our results support a role of semiochemical carriers for NPC2 proteins in insects and indicate such proteins as new targets for insecticide-free pest population control.